A Tax-Based Approach to Slowing Global Climate Change - Aldy, Joseph E.; Ley, Eduardo; Parry, Ian (2012)
This paper discusses the design of CO2 taxes at the domestic and international level and the choice of taxes versus cap and trade. There is a strong case for taxes on uncertainty, fiscal, and distributional grounds, though this critically hinges on policy specifics and how revenues are used. The efficient near-term tax is at least $5-$20 per ton of CO2 and the tax should be imposed upstream with incentives for downstream sequestration and abatement of other greenhouse gases. At the international level, a key challenge is the possibility that emissions taxes might be undermined through offsetting changes in other energy policies.